A novel compound VSC2 has anti‐inflammatory and antioxidant properties in microglia and in Parkinson's disease animal model. (15th December 2014) - Lee, Ji Ae; Kim, Ji Hyun; Woo, Seo Yeon; Son, Hyo Jin; Han, Se Hee; Jang, Bo Ko; Choi, Ji Won; Kim, Dong Jin; Park, Ki Duk; Hwang, Onyou
<x xml:space="preserve">Abstract</x> Background and Purpose Neuroinflammation through microglial activation is involved in the pathogenesis of neurodegenerative diseases including Parkinson's disease (PD), a major neurodegenerative disorder characterized by dopaminergic neuronal death in the substantia nigra. We examined our novel synthetic compound VSC2 for its anti‐inflammatory properties towards development of a PD therapy. Experimental Approach We tested the effects of VSC2 on production of various NF‐κB‐dependent proinflammatory molecules and Nrf2‐dependent antioxidant enzymes in BV‐2 microglia and in vivo. Key Results The vinyl sulfone compound, VSC2, most effectively suppressed the production of NO in LPS‐activated microglia. It also down‐regulated expression of inducible NOS (iNOS), COX‐2, IL‐1β and TNF‐α and inhibited nuclear translocalization and transcriptional activity of NF‐κB. VSC2 increased total and nuclear Nrf2 levels, induced Nrf2 transcriptional activity and was bound to Keap1 with high affinity. Expression of the Nrf2‐regulated antioxidant enzyme genes NAD(P)H quinone oxidoreducase‐1 (NQO‐1), haem oxygenase‐1 (HO‐1) and glutamylcysteine ligase (GCL) were up‐regulated by VSC2. In the MPTP mouse model of PD, oral administration of VSC2 decreased the number of activated microglia in the substantia nigra, lowered the levels of iNOS, COX‐2 and IL‐1β, and protected the dopaminergic neurons. VSC2 also elevated the levels of NQO1, HO‐1, GCL and Nrf2 in the nigrostriatal area. Conclusions and Implications VSC2 has both anti‐inflammatory and antioxidant properties and prevented neuroinflammation in microglia and in an animal model of PD. This suggests VSC2 as a potential candidate for PD therapy.